Optical/γ-ray blazar flare correlations: understanding the high-energy emission process using ASAS-SN and Fermi light curves - de Jaeger T; Shappee BJ; Kochanek CS; Hinkle JT; Garrappa S; Liodakis I; Franckowiak A; Stanek KZ; Beacom JF; Prieto JL (OXFORD UNIV PRESS, 2025)
Using blazar light curves from the optical All-Sky Automated Survey for Supernovae (ASAS-SN) and the gamma-ray Fermi-LAT telescope, we performed the most extensive statistical correlation study between both bands, using a sample of 1180 blazars. This is almost an order of magnitude larger than other recent studies. Blazars represent more than 98 per cent of the AGNs detected by Fermi-LAT and are the brightest gamma-ray sources in the extragalactic sky. They are essential for studying the physical properties of astrophysical jets from central black holes. Ho we ver, their gamma-ray flare mechanism is not fully understood. Multiwavelength correlations help constrain the dominant mechanisms of blazar variability. We search for temporal relationships between optical and gamma-ray bands. Using a Bayesian Block Decomposition, we detect 1414 optical and 510 gamma-ray flares, we find a strong correlation between both bands. Among all the flares, we find 321 correlated flares from 133 blazars, and derive an average rest-frame time delay of only 1.1(-8.5)(+7.1) d, with no difference between the flat-spectrum radio quasars, BL Lacertae-like objects or low, intermediate, and high-synchrotron peaked blazar classes. Our time-delay limit rules out the hadronic proton-synchrotron model as the driver for non-orphan flares and suggests a leptonic single-zone model. Limiting our search to well-defined light curves and removing 976 potential but unclear "orphan' flares, we find 191 (13 per cent) and 115 (22 per cent) clear "orphan' optical and gamma-ray flares. The presence of "orphan' flares in both bands challenges the standard one-zone blazar flare leptonic model and suggests multizone synchrotron sites or a hadronic model for some blazars.